Falhas nos processos de leilões de transmissão: os efeitos da interdependência e restrição de capacidade - MOTTA, Lucas Varjão (2017)
The Brazilian Electricity Sector adopted the auction mechanism to allocate Power Transmission assets. Using auctions the Brazilian Power Transmission Sector faced an intense expansion in the last decade. Since 2001 more than 61.000 km of power lines was contracted. The auctions’ results are impacted by interdependence and the capacity constraint. We investigate the reasons behind the growing rate of failures observed in the Brazilian Power Transmission Auctions (BPTA). More specifically, we analyze the cases of Empty auctions and Removed projects in the BPTA. We also analyze the policies utilized by the regulator as a measure to deal with the issues and enhance the objects attractiveness. We attempt to answer the following question: "How well are auctions allocating projects in the Brazilian Transmission Sector (BTS)?". We develop a theoretical model to evaluate these issues in a procurement auction sequence. The theoretical model shows that the joint action of interdependence and of capacity restriction decreases the competitiveness of the participants and the payoff of auctioneers. We also study what happens after the projects are contracted. We conclude that the transmission sector is facing a management issue as the government has difficulties to contract and the contracted projects are not usually delivered in time. We verify a significant and increasing gap between the planned and the executed projects. We found that the interdependence affected the probability of winning and the behavior of the bidding. Finally we empirically check for reasons that are affecting bidders participation. We verify that Interdependency and Capacity Constraint affects participation decision and winning likelihood. We suggest policies based on the results achieved.